(untitled) (Boca Raton, Fla., 1984)
This text provides a clear exposition of genetic principles and problems with comprehensive, up-to-date references. Specialists who have collaborated closely with industry give an inside authentic view of the genetics and breeding of industrial microorganisms such as yeasts, filamentous fungi, actinomycetes, pseudomonads, and other bacteria of major industrial significance. This book will be especially valuable to many professionals in the field of microbial genetics.
Keywords: Microbial genetics,Industrial microbiology,Di truyền vi sinh vật